Strategi dan Proyeksi Keuangan untuk Proyek Bisnis Hub Kertas Daur Ulang - Andre, Andre; Indradewa, Rhian; Yanuar Rahmat Syah, Tantri; Kustiawan, Unggul (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
Recycled Paper Hub is a business unit mainly focus in processing recycled paper sorted from local collector who also act as supplier such as waste paper collected from traditional market, ex-packaging collected from home industry and household waste, etc. Recycled Paper Hub primary goal is to participate in the sustainable business by contributing to the economy of the surrounding community along with a commitment to maintaining a green environment. In order to achieve this goals, Recycled Paper Hub conduct business development strategy which include financial planning and projection. The method used in this research is using data that has been previously collected and analyzed within 3 stages, namely : data collection (internaly from company that the author is working, then data filtering, and finally data presentation along with conclusion. Within this research, financial planning is distributed in 5 main pillars, that is : Financial Objectives, ,Financial Elements, Financial Projections, Feasibility Analysis, and Performance Analysis.